Boosting electricity generation associated with Saudi Arabi buildings using PCM and PV cells on walls and roof leading to a sustainable building - Naeim Farouk; SamahG.Babiker; Umar F. Alqsair (Case Studies in Thermal Engineering)
In Saudi Arabia, where the majority of regions receive a minimum incident shortwave solar energy exceeding 4 kWh/(m2. year), there is a high potential for electricity generation and simultaneously, a challenge in building cooling. In this study, by adding photovoltaic (PV) on the roof and wall, as well as using phase change material (PCM) inside the walls, electricity production and energy consumption of Saudi residential buildings were investigated. Taking into account the effects of radiation on vertical and horizontal envelopes as well as phase change in PCM, the energy equation was solved using DesignBuilder to specify hourly energy consumption and electricity generation. When installing PV cells at the optimal tilt, incoming radiation to the cells increases. However, creating shadows on subsequent rows of cells diminishes the effective PV surface area. Surprisingly, calculations revealed that if PV cells are installed at zero angle, owing to installing more PV cells, up to 31 % extra electricity is produced than when installed at the optimal tilt. As a side effect, the cooling load decreases by 5.1 % due to reduced radiation intensity on the roof. The orientation of the walls significantly impacts both phase change material (PCM) and PV-associated electricity generation. Placing PCM on the east wall optimizes its performance, while walls containing PV panels perform best when facing south. To further enhance cooling and reduce electricity demand, phase change material was incorporated into both the roof and wall, resulting in a 2 % reduction in overall electricity demand. Notably, in eight major populated areas across Saudi Arabia, under the constraint of the constant PV cell area, installing PV cells on the roof proves three times more advantageous than placing them on the walls.